Forty years of research on factors influencing ethical decision making: Establishing a future research agenda - Luca Casali, Gian; Perano, Mirko (Journal of business research, 2021)
The purpose of this study is to review, synthesize and critique the voluminous, multidisciplinary literature on factors influencing ethical decision making (EDM) by adopting a unique qualitative approach. The main results of this paper initially involve identifying 42 factors provided in the past forty years of research as potentially influencing EDM (provided by four main systematic literature review papers on EDM). We adopt the Ebb and Flow Visualization to summarize and classify those 42 factors by using two main criteria descripted in the paper. The results clearly show that in over forty years of literature, there are factors that have received much more research attention than others and that some factors have been identified more influential than others. A proposed future research agenda has been designed providing possible activities to further investigates the impact of factors influencing EDM. Finally, theoretical and managerial implications are also provided in the conclusion section.